Rewind - O'Doherty, Carolyn (Boyds Mills Press, an imprint of Highlights, 2018)
In a world where spinners can freeze and rewind time but are tightly controlled by the government, sixteen-year-old Alex is a spinner paired with Agent Ross to help catch a dangerous criminal.